2013
DOI: 10.1039/c3nr33142c
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of Cu and Cu@Cu–Ni nanocubes and nanowires in hydrophobic solution in the presence of nickel and chloride ions

Abstract: A highly shape selective synthesis of Cu and Cu@Cu-Ni nanocubes and nanowires has been developed by modulating the coordination chemistry of transition metal ions with a trioctylphosphine (TOP)-Cl(-) ligand pair in oleylamine under mild organic solvent conditions. The as-prepared nanocubes have a face-centered cubic (fcc) phase and are covered by six {100} facets, whereas the as-prepared nanowires have a multi-twinned structure and grow along the [110] direction. Both the Ni(2+) and Cl(-) ions, along with TOP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
105
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 47 publications
7
105
0
Order By: Relevance
“…In synthesis of Cu nanocubes, selected additives such as NH 4 Cl [26], trioctylphosphine (TOP) [27], and trioctylphosphine oxide [21] have proven to be effective for fabrication of cubic morphology. Recently, Yang et al [28] reported that truncated Cu nanocubes with average edge length of 75 nm could be synthesized by rapidly injecting a mixture of CuCl and octadecylamine (ODA) into hot oleylamine/TOP solution.…”
Section: Introductionmentioning
confidence: 99%
“…In synthesis of Cu nanocubes, selected additives such as NH 4 Cl [26], trioctylphosphine (TOP) [27], and trioctylphosphine oxide [21] have proven to be effective for fabrication of cubic morphology. Recently, Yang et al [28] reported that truncated Cu nanocubes with average edge length of 75 nm could be synthesized by rapidly injecting a mixture of CuCl and octadecylamine (ODA) into hot oleylamine/TOP solution.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the light has been largely blocked by the thick media. Recently, metal nanowires include Ag NWs24, Cu NWs1925 and Cu@Ni core-shell NWs26, have been synthesized through chemical solution route. These metal NWs in the form of inks were then imprinted onto substrates to form desired TEs.…”
mentioning
confidence: 99%
“…However, this technique uses high concentrations of sodium hydroxide (NaOH) and requires stringent washing technique to remove the alkali that could hamper the conductivity of Cu NWs due to surface oxidation. On the other hand, long alkyl amine-mediated synthesis of Cu NWs has gained importance due to the possibility of dispersing and storing the products in organic solvents that could avoid rapid oxidation [19][20][21][22]. In this method, alkyl amines function as the reducing, protecting, and growth-controlling agent.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the research on the development of Cu NWs are on the rise due to the availability of cheap and abundant resources, high electrical properties, and low migration problem despite the fact that Cu has showed low stability in moist and oxidizing atmospheres [4][5][6][7][8]. Consequently, several physical and chemical routes have been developed to synthesize Cu NWs; however, in most cases, the chemical routes are considered due to simplicity and scalability of these techniques in contrast to other routes [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Among the developed chemical techniques, aqueous synthetic route using hydrazine as the reducing agent is researched intensively [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%